Lived Experiences of Corruption in Public Service Delivery: A Phenomenological Study in Butwal, Nepal (GMMC Journal of Interdisciplinary Studies, 2025)
The level of corruption in Nepal in the public services is still eroding institutions and the trust of the people. This paper employed phenomenology and focused on how the general public perceive and feel corruptness within the government agencies. It presumes that the experience of users can shed light on how corruption is continued to exist. We applied phenomenology in order to investigate actual experiences of corruption. Convenience sampling was used to select five service users of government agencies from Butwal Sub-Metropolitan City, who were interviewed using semi-structured questions. Our interview was manually coded and employing of principal-agent, collective action, institutional, and game theories to interpret the fi ndings. Four main themes were found. The former: the users perceive corruption as a time-saving tool. They perceive informal payments as an instrument of accelerating processes and lessening the losses incurred due to the bureaucracy. The second theme: bureaucracy is so complicated, numerous documents, and lack of transparency present circumstances such that promote corruption. The third theme: corruption is a new way of life. Businesses and citizens depend on informal payments in terms of how services should operate. Corrupt behaviour is accepted by people though they are aware that the system is being damaged by it. The fourth theme: the users are extremely intensified and discontented with the government and officials attribute the bad progress in economy to the overbearing prevalence and low regulation. The paper demonstrates that corruption does not increase because the laws against corruption are not in place; it is just a preference of the structures that makes people believe that corruption is a reasonable response to bureaucratic hurdles and government interference. Reforms should be done to cut down corruption, ease the processing, increase transparency, accountability, and reasonable compensation; not just to penalize individuals in already corrupt system.